Impact of Multi-Defect Coupling Effects on the Safety of Shield Tunnels and Cross Passages - Xiaokai Niu; Hongchuan Xing; Wei Li; Wei Song; Zhitian Xie (Buildings)
As urban rail transit networks age, understanding the synergistic impacts of multi-defect interactions on tunnel structural safety has become critical for underground infrastructure maintenance. This study investigates defect interaction mechanisms in shield tunnels and cross passages of Beijing Metro Line 8, integrating field monitoring, numerical simulations, and Bayesian network analysis. Long-term field surveys identified spatiotemporal coupling characteristics of four key defects—lining leakage, structural voids, material deterioration, and deformation—while revealing typical defect propagation patterns such as localized leakage at track beds and drainage pipe-induced voids. A 3D fluid–solid coupling numerical model simulated multi-defect interactions, demonstrating that defect clusters in structurally vulnerable zones (e.g., pump rooms) significantly altered pore pressure distribution and intensified displacement, whereas void expansion exacerbated lining uplift and asymmetric ground settlement. Stress concentrations were notably amplified at tunnel–cross passage interfaces. The Bayesian network risk model further validated the dominant roles of defect volume and burial depth in controlling structural safety. Results highlight an inverse correlation between defect severity and structural integrity. Based on these findings, a coordinated maintenance framework combining priority monitoring of high-stress interfaces with targeted grouting treatments is proposed, offering a systematic approach to multi-defect risk management that bridges theoretical models with practical engineering solutions.